Insight in Alzheimer's disease and its relation to psychiatric and behavioral disturbances. (14th May 2013) - Horning, Sheena M.; Melrose, Rebecca; Sultzer, David
<x xml:space="preserve">Abstract</x> Objective Individuals suffering from Alzheimer's disease (AD) often have impaired awareness or a lack of insight into their cognitive deficits and functional abilities, especially in the later stages of the disease. Previous research has documented a relationship between depression and insight in AD, such that greater awareness of one's disease has been associated with a higher degree of depression. However, little is known about the relationship between insight, cognitive decline, and other psychiatric or behavioral problems associated with AD. Methods This study included 107 outpatients who met criteria for probable AD. Instruments included the Neurobehavioral Rating Scale, the Apathy Evaluation Scale, and the mini mental state exam. A series of hierarchical regression analyses were conducted to determine the relationship between insight and depressed mood, anxiety, psychosis, apathy, agitation, and behavioral retardation in AD patients after controlling for cognitive skills. Results Insight was found to significantly predict depressed mood, anxiety, and apathy even after controlling for global cognition. Greater insight was found to be associated with depressed mood and anxiety. However, impaired insight was associated with higher levels of apathy. Conclusion Insight may be differentially related to mood symptoms and apathy within AD, such that patients with intact insight are more depressed, whereas patients with impaired insight are more apathetic. This suggests that assessment of insight in AD may complement the clinical evaluation of depression and apathy in AD and help guide the most appropriate interventions. Published 2013. This article is a U.S. Government work and is in the public domain in the USA.